PERCEPÇÕES DOS USUÁRIOS DE TELEFONIA MÓVEL CELULAR QUANTO À FIDELIZAÇÃO E PERMANÊNCIA DE CLIENTES NAS OPERADORAS NO MUNICÍPIO DE CAMPOS DOS GOYTACAZES, RJ - Tadeu Ribeiro Sousa, Tiago; Shimoya, Aldo; Shimoda, Eduardo; da Silva Oliveira, Érik (LINKSCIENCEPLACE, 2026)
Increasingly often associated with new mobile telephony, due to increased demand made by customers and users of these services. Thus, the aim of this paper is to show through the perceptions of users and customers of mobile operator’s vision of ourselves in relation to retention and loyalty in the municipality of Goytacazes - RJ. For the assessment of customer perceptions, a questionnaire was administered to 400 people, through interviews, most of the questions applied used the Likert scale. Statistical analyzes performed included obtaining the means and standard deviations. Mean test by Tukey’s test were also performed and the correlation analysis was performed between the responses using the Spearman correlation. Generally realized - that the issue of financial items offered by mobile operators, are the main contributors to the permanence and faithfulness on the part of users. Items within the financial issue, by Spearman correlation, we can identify the item " promotions ", was the most assists in the evaluation for the permanence and loyalty of mobile operators in the municipality of Goytacazes-RJ.